2016
DOI: 10.1080/1478422x.2016.1139319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracellular polymeric substances isolated fromVibrio natriegenson corrosion of carbon steel in seawater

Abstract: Extracellular polymeric substances (EPS) are isolated from marine Vibrio natriegens (V. natriegens) by a cation exchange resin method. The influences of EPS concentration and corrosion time on the corrosion of carbon steel in seawater are investigated. The results demonstrate that EPS are capable of forming a protective film on the surface of carbon steel in seawater, which retards the diffusion of dissolved oxygen and inhibits the reduction of oxygen on the cathode. In addition, the efficiency of corrosion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Also other high molecular weight molecules such as proteins, nucleic acids and lipids which are produced for biofilm formation (Wingender et al, 1999) may impact the rheology of the medium. These extracellular polymeric substances were already identified in a biofilm formed by V. natriegens on steel in sea water (Dong et al, 2016). However, in our planktonic cultures we could not determine the presence of significant amounts of protein using the Bradford assay with bovine serum albumin as standard.…”
Section: Discussionmentioning
confidence: 86%
“…Also other high molecular weight molecules such as proteins, nucleic acids and lipids which are produced for biofilm formation (Wingender et al, 1999) may impact the rheology of the medium. These extracellular polymeric substances were already identified in a biofilm formed by V. natriegens on steel in sea water (Dong et al, 2016). However, in our planktonic cultures we could not determine the presence of significant amounts of protein using the Bradford assay with bovine serum albumin as standard.…”
Section: Discussionmentioning
confidence: 86%
“…EPS can adsorb on the metal surface and form a biofilm, which acts as a protective layer, hinders the transmission of oxygen, and separates a metal surface from a corrosive environment, thus, metal corrosion is inhibited [ 53 , 54 , 124 , 125 , 126 , 127 ]. The negatively charged functional groups in EPS, such as -NH 2 , -COOH, -C-O-C, and -OH, first adsorb positively charged metal ions to form complexes.…”
Section: Eps and Biocorrosionmentioning
confidence: 99%
“…Existing studies have found that some functional groups in EPS will complex metal ions (iron ions, copper ions, etc.) and, thus, accelerate the dissolution of the anode causing corrosion [ 53 , 54 ]. However, there are also studies showing that the attachment of EPS has an inhibitory effect on the corrosion of a metal, mainly because EPS adsorb on the surface of a material and form a protective film.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that EPS promotes corrosion, however, researchers also have shown beneficial microorganisms attached to metal surfaces interact with the liquid flow environment (Dong et al 2016, Li et al 2019a, Suma et al 2019) forming a biofilm on the surface of the metal. This microbiologically influenced corrosion inhibition (MICI) may protect carbon steel surfaces by inhibiting corrosion and be used as an alternative method to combat corrosion (Xu et al 2020).…”
Section: Introductionmentioning
confidence: 99%